Autotrophic nitrogen removal over nitrite in a sponge-bed trickling filter. (July 2015) - Sánchez Guillén, J.A.; Jayawardana, L.K.M.C.B.; Lopez Vazquez, C.M.; de Oliveira Cruz, L.M.; Brdjanovic, D.; van Lier, J.B.
Highlights: Anammox process under natural air convection is feasible in sponge-bed reactors. Nitrogen removal was consequence of coexistence of nitrifiers and anammox bacteria. Oxygen from the influent and the air governed the performance of the reactors. Sponge-bed reactors showed robustness to the nitrogen loading rate fluctuations. A nitrogen removal of 52–54% was reached in only 100 days and 1.71–2.96 h of HRT. Abstract: Partial nitritation in sponge-bed trickling filters (STF) under natural air circulation was studied in two reactors: STF-1 and STF-2 operated at 30 °C with sponge thickness of 0.75 and 1.50 cm, respectively. The coexistence of nitrifiers and Anammox bacteria was obtained and attributed to the favorable environment created by the reactors' design and operational regimes. After 114 days of operation, the STF-1 had an average NH4 + -N removal of 69.3% (1.17 kg N/m 3 sponge d) and a total nitrogen removal of 52.2% (0.88 kg N/m 3 sponge d) at a Nitrogen Loading Rate (NLR) of 1.68 kg N/m 3 sponge d and Hydraulic Retention Time (HRT) of 1.71 h. The STF-2 showed an average NH4 + -N removal of 81.6 % (0.77 kg N/m 3 sponge d) and a total nitrogen removal of 54% (0.51 kg N/m 3 sponge d), at an NLR of 0.95 kg N/m 3 sponge d and HRT of 2.96 h. The findings suggest that autotrophic nitrogen removal over nitrite in STF systems is a feasible alternative.